An Early Look at a Time-Lapse 3D VSP - Campbell, A; Nutt, L.; Ali, S.; Dodds, Kevin; Urosevic, Milovan; Pevzner, Roman; Sharma, S. (EAGE, 2011)
In 2007 Australian Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) started a project to evaluate the available technology for monitoring the movement of CO2 in an underground reservoir. In stage one of this project CO2 and methane are being produced in a nearby well, then the CO2/CH4 is being injected back down a second well into a depleted gas sand. The movement of the CO2 up-dip needs to be remotely monitored. One of the technologies being evaluated to monitor the movement of the CO2 is 3D VSP. The CRC-1 injector well is instrumented with 10 3C downhole accelerometers. A baseline 3D VSP survey was shot around this well in late 2007 and was followed by a repeat survey in 2010. We hope to monitor the movement of CO2 around the CRC-1 well by observing changes in the time-lapse signature.